Water hyacinth‐derived activated carbon/NiO nanocomposite as a facile electrode material for high performance supercapacitor. (1st April 2017) - Qiu, Zehai; Huang, Tianfu; Zhao, Chenhao; Luo, Jiangshui; Hu, Zhibiao
Abstract : Water hyacinth‐based activated carbon (denoted as WHc) decorated with porous petaloid‐like nano‐NiO has been fabricated by hydrothermal method. The hierarchical petaloid‐like NiO composed of numerous nanoplates is uniformly covered on the surface of WHc. Such unique nanocomposite exhibits excellent electrochemical performances: a high specific capacitance of 249.5 F g −1, a good rate capability and an excellent cycling performance with 78.35% retention after 1000 cycles can be obtained at a current density of 1 A g −1 . These results suggest that the porous petaloid‐like WHc/NiO nanocomposite (denoted as WHc/NiO) may be promising for practical applications for supercapacitors.